2022
DOI: 10.1038/s41598-022-10052-y
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities and phenolic compounds of olive oil mill wastewater from Abani, endemic Algerian variety

Abstract: The current study aimed to determination of cytotoxicity, antioxidant, anti-inflammatory, anti-hemolytic, and anticoagulant activities of phenolic compounds extracted from olive oil mill wastewater (OMW) issue from the cold extraction of olive oil from Khenchela eastern in Algeria. The LC–MS (liquid chromatography–mass spectrometry) results were revealed the presence of 20 phenolic compounds in the extract of OMW and mostly consisted of Kaempferol, 4,5-di-O-caffeoyquinic acid, quinic acid, and caffeic acid. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Proton loss and free radical neutralization are the key mechanisms through which phenolic substances exhibit antioxidant effects (47). Moreover, it has been reported that the polyphenolic metabolites derived from plants also exhibit high antiinflammatory as well as anticoagulant properties (48). In this study, the aqueous extract possessed a significant concentration of phenols and flavonoids, indicating the strong antioxidant activity of garlic.…”
Section: Discussionmentioning
confidence: 56%
“…Proton loss and free radical neutralization are the key mechanisms through which phenolic substances exhibit antioxidant effects (47). Moreover, it has been reported that the polyphenolic metabolites derived from plants also exhibit high antiinflammatory as well as anticoagulant properties (48). In this study, the aqueous extract possessed a significant concentration of phenols and flavonoids, indicating the strong antioxidant activity of garlic.…”
Section: Discussionmentioning
confidence: 56%
“…The comparison of the IC50 values for the extracts with those of the standard antioxidants (Ascorbic acid, Trolox, and BHT) allows for the evaluation of the extracts' antioxidant potential relative to well-known synthetic antioxidants. A lower IC50 value suggests that the extracts have strong antioxidant capabilities and are effective in neutralizing free radicals (Gueboudji et al, 2022a).…”
Section: Dpph Free Radical-scavenging Activitymentioning
confidence: 99%
“…It was measured according to the method described by (Gueboudji et al, 2022a) with some adjustment. In this study, blood was collected from a healthy volunteer who had not taken non-steroidal anti-inflammatory drugs (NSAIDs) for two weeks.…”
Section: Membrane Stabilizing Potential (Msp)mentioning
confidence: 99%
“…The biological activities of phenolic compounds are exploited in pharmaceutical industries because of their antiinflammatory, antioxidant, anti-hypertensive, anti-microbial, hepatoprotective properties, antidiabetic, and anticancer, etc. [11]. Arctigenin, arctiin and trachelogenin have been reported as anti-HIV, anticancer [12][13].…”
Section: Secondary Metabolitesmentioning
confidence: 99%